2022
DOI: 10.1097/md.0000000000032004
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognostic risk factors of cervical cancer patients aged ≤35 years old

Abstract: We aimed to explore the clinicopathological characteristics and prognostic risk factors of cervical cancer in patients aged ≤35 years. A total of 256 cervical cancer patients treated at Anhui Medical University Affiliated Maternity and Child Health Hospital and The First Affiliated Hospital of Anhui Medical University from January 2016 to October 2018 were divided into ≤35-year-old (n = 136) and >35-year-old (n = 120) groups. Their clinicopathological characteristics and 3-year cumulative disease-free survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Many studies analyzed prognostic factors, suggesting that for patients receiving NACT-RS, age, the number of lymph node metastases, focal diameter, LVSI, and disease stage are all prognostic factors [15][16][17][18]. In this study, the patients' tumor stage, tumor diameter, SCC level, imaging lymph node status, parastatal involvement, pathological lymph node metastasis status, LVSI and deep cervical interstitial infiltration were included in Cox risk regression, and the results showed that parastatal infiltration and LVSI were risk factors affecting 2-year PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies analyzed prognostic factors, suggesting that for patients receiving NACT-RS, age, the number of lymph node metastases, focal diameter, LVSI, and disease stage are all prognostic factors [15][16][17][18]. In this study, the patients' tumor stage, tumor diameter, SCC level, imaging lymph node status, parastatal involvement, pathological lymph node metastasis status, LVSI and deep cervical interstitial infiltration were included in Cox risk regression, and the results showed that parastatal infiltration and LVSI were risk factors affecting 2-year PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate-risk factors include LVSI (+), deep stromal invasion, and larger primary tumors 19 . Previous studies have demonstrated that all of these risk factors are prognostically associated with lymph node-positive cervical cancers [20][21][22][23] . Based on these findings, the addition of adjuvant therapy should be recommended.…”
Section: Discussionmentioning
confidence: 99%